Pengembangan Perencanaan Metode dan Strategi Pembelajaran PAI Berbasis Lingkungan - Sulwana, Siti; Nasrun Harahap (TAUJIH: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (PAI) learning has tended to be theoretical, regardless of the real-life context and the environment around students. Academic anxiety arises when the learning process only focuses on cognitive aspects, so that it does not encourage students to internalize Islamic values in daily life in a contextual and applicative manner. This requires development in the planning of PAI learning methods and strategies that are more integrative and responsive to the student learning environment. The objectives of this research are first, to analyze methods and strategies in PAI learning, and second, to formulate the process of developing environment-based PAI learning methods and strategies, with a focus on two aspects, namely the characteristics of the environment as a source of learning and the integration of Islamic values in the interaction of students with their environment. This research uses a qualitative approach with the library research method, as well as reviews the latest literature related to the concept of environmental pedagogy and PAI learning development. The results of the study show that PAI learning planning that utilizes the surrounding environment as a medium and learning resource can increase active participation, holistic understanding, and contextual internalization of Islamic values. Environment-based learning strategies have also been proven to encourage the growth of ecological awareness within the framework of Islamic spirituality. These findings make a conceptual contribution to the development of PAI learning models that are more adaptive to students' social and ecological dynamics.